Anatomical peculiarities of wheat roots under cadmium contaminated conditions (Experimental biology, 2015)
It was studied the anatomical structure of roots of 5 wheat cultivars: Shagala, Kazakhstanskaya-3, Kazakhstanskaya rannaya, Melturn and Kayr under cadmium contaminated conditions (0,15 мM and 0,3 мМ CdSO4). In Melturn and Shagala cultivars the level of tolerance on growth parameters is correlated with anatomical changes in roots structure